EFFICIENCY OF THE METHOD OF VOLITIONAL DECREASE OF BREATH RATE OF CURATIVE-GROUP STUDENTS (Proceedings of the YSU B: Chemical and Biological Sciences, 2005)
Using the method of volitional optimal decrease of minute volume of breathing leads to activation of organism’s protective mechanisms. This method was used in the groups of curative physical training. It was revealed that this method is very effective for the increase of mental and physical work ability of students with pathological background of different physiological functions.
Keywords: minute volume of breathing; organism’s protective mechanisms; groups of curative physical training